Report of the Fuel and Power Sector - Planning Commission (Planning Commission, 1974)
Fuel and Power are the essential ingredients to present day economy. A country like India, whose economic is primarily based on agriculture- and partly on industry, the importance of the fuel and power sector to die economic growth cannot be over emphasised. Today, the biggest hurdle to economic growth all over the world is not so much the scarcity of raw mate rails but energy. All the countries of the world, including developed, developing and under developed, are lacing energy shortages. The severity of the problem in different countries is only relative.
National Committee on Science and Technology
National Committee on Science and Technology